2014
DOI: 10.7314/apjcp.2014.15.6.2889
|View full text |Cite
|
Sign up to set email alerts
|

Association of DR4 (TRAIL-R1) Polymorphisms with Cancer Risk in Caucasians: an Updated Meta-analysis

Abstract: Death receptor 4 (TRAIL-R1 or DR4) polymorphisms have been associated with cancer risk, but findings have been inconsistent. To estimate the relationship in detail, a meta-analysis was here performed. A search of PubMed was conducted to investigate the association between DR4 C626G, A683C and A1322G polymorphisms and cancer risk, using odds ratios (ORs) with 95% confidence intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…No predictions of the effects of this SNP on protein function were identified by SIFT or PolyPhen-2. While studies of the associations between TNFRSF10A rs17620 and fatigue were not found, TRAIL polymorphisms are associated with increased cancer risk [135, 136]. In our study, patients who were heterozygous or homozygous for the rare C allele were predicted to have a steeper trajectory of morning fatigue scores that suggests clinically meaningful increases in fatigue at four of the six assessments (i.e., assessments 2, 4, 5 and 6) (Figure 3A).…”
Section: Discussionmentioning
confidence: 53%
“…No predictions of the effects of this SNP on protein function were identified by SIFT or PolyPhen-2. While studies of the associations between TNFRSF10A rs17620 and fatigue were not found, TRAIL polymorphisms are associated with increased cancer risk [135, 136]. In our study, patients who were heterozygous or homozygous for the rare C allele were predicted to have a steeper trajectory of morning fatigue scores that suggests clinically meaningful increases in fatigue at four of the six assessments (i.e., assessments 2, 4, 5 and 6) (Figure 3A).…”
Section: Discussionmentioning
confidence: 53%
“…The C-G single nucleotide polymorphism in exon 4 of DR4 gene is the most studied polymorphism which has recently been linked with cancer in Caucasian susceptibility (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…They reported that there was no association between C626G polymorphism and the risk of cancer in all genetic models when all the eligible studies were pooled into the metaanalysis (Chen et al, 2009). But, in a recent meta-analysis, it has been reported that TRAIL DR4 C626G and A683C polymorphisms were indeed associated with cancer risk (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The DR4 gene is highly polymorphic. The trio ‐C626G, ‐A683C, and ‐A1322G polymorphisms of TRAIL‐R1 gene were previously studied in different cancers; however, few reports are available for HCC especially in Arab‐African nations. DR4‐C626G polymorphism occurs in the ectodomain region of DR4, whereas the DR4‐A683C and DR4‐A1322G polymorphisms occur in the extracellular cysteine‐rich domain and DD region of DR4, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…As for DR4‐A1322G polymorphism, it is an adenine to guanine transition at nucleotide 1322 that results in the conversion of lysine into arginine. These genetic variants may lead to alterations in the TRAIL‐binding domain and, thus, alter DR4 affinity for TRAIL …”
Section: Introductionmentioning
confidence: 99%